FOXM1 Modulates Cisplatin Sensitivity by Regulating EXO1 in Ovarian Cancer - Zhou, Jinhua; Wang, Yunfei; Wang, You; Yin, Xia; He, Yifeng; Chen, Lilan; Wang, Wenwen; Liu, Ting; Di, Wen (PloS one, 2014)
Cisplatin is commonly used in ovarian cancer chemotherapy, however, chemoresistance to cisplatin remains a great clinical challenge. Oncogenic transcriptional factor FOXM1 has been reported to be overexpressed in ovarian cancer. In this study, we aimed to investigate the potential role of FOXM1 in ovarian cancers with chemoresistance to cisplatin. Our results indicate that FOXM1 is upregulated in chemoresistant ovarian cancer samples, and defends ovarian cancer cells against cytotoxicity of cisplatin. FOXM1 facilitates DNA repair through regulating direct transcriptional target EXO1 to protect ovarian cancer cells from cisplatin-mediated apoptosis. Attenuating FOXM1 and EXO1 expression by small interfering RNA, augments the chemotherapy efficacy against ovarian cancer. Our findings indicate that targeting FOXM1 and its target gene EXO1 could improve cisplatin effect in ovarian cancer, confirming their role in modulating cisplatin sensitivity.